Peran Asas Umum Pemerintahan yang Baik terhadap Pencabutan Izin Usaha Asuransi - Priskila Paulina Kurnia; Christine ST. Kansil (Syntax Literate, 2023)
Every Government Institution, in carrying out its administrative duties and authority, is based on several principles, one of which is the General Principles of Good Government (AUPB). AUPB is a principle used as a reference for the use of authority for Government Officials in issuing Decisions and/or Actions in administering government. One of the government institutions that functions to supervise the financial sector is the Financial Services Authority. The researcher will solve the legal issues surrounding the role of general principles of good governance in the revocation of insurance business licenses using normative juridical methods, because the author wants to find answers to these legal issues based on norms or legal or statutory aspects. This legislative approach is used by researchers to examine statutory regulations and other legal rules relating to insurance in order to answer problems in the form of the role of general principles of good governance in the revocation of insurance business permits. There are 8 (eight) points covered by the General Principles of Good Government, namely legal certainty, usefulness, impartiality, accuracy, non-abuse of authority, openness, public interest and good service. The legal consequences that occur if an insurance company has had its business license revoked are that all business activities are stopped and they are required to hold a General Meeting of Shareholders (GMS) and also form a Liquidation Team to compensate the losses of the injured parties. Apart from violations committed by insurance companies contained in POJK No. 9/POJK.05/2021, the OJK must also take the AUPB into consideration before issuing a decision, especially in this case if the OJK revokes the business license of an insurance company.